A velvet worm (Onychophora: Peripatidae) feeding on a free ranging spider in Sierra Llorona, Panama (UNED Research Journal, 2018)
Onychophoran worms seldom attack spiders because spiders are agile and dangerous prey. Here we report an onychophoran feeding on a spider (possibly a Ctenidae) in Sierra Llorona, Colón, Panamá (9,35863°-79,70287°; altitude 491 m).
Keywords: Neotropical invertebrates; adhesive net; private reserve; tropical rainforest